Effect of microwave heating damage on the electrical, thermal and mechanical properties of fibre-reinforced cement mortars. (20th October 2018) - Borinaga-Treviño, R.; Orbe, A.; Norambuena-Contreras, J.; Canales, J.
Highlights: Microwave heating harm on steel fibre-reinforced and plain mortars was measured. Microwave heating reduces flexural strength on non-reinforced mortars. Steel fibres reduced mechanical damage on reinforced mortars. Thermal and electrical tests did not detect the mechanical damage in any case. Abstract: Nowadays, refurbishing of existing structures has gained interest in order to reduce both the construction materials used and the construction and demolition waste production. For that purpose, there are several methods for demolishing the damaged parts, but most of the alternatives involve high noise and dust production, which are in contraposition when structures are in urban areas. Among all the existing methods, this paper studies the possibility of using microwave heating as a demolition method, either by damaging the bulk material or the mortar to concrete interface. With that in mind, the effect of microwave heating time (range 120–600 s) on the physical, thermal, electrical, mechanical and bonding properties of steel fibre-reinforced and non-reinforced cement mortars was analysed. The aim of the paper is to establish possible correlations between the mentioned properties and the damage level caused by microwave heating. Although the results prove that pore pressure increment due to microwave heating can cause the reduction of flexural strength up to the rupture of the specimens, this fact cannot be extended to all the properties or mortar types. The fibre reinforcement plays a key role to restrain the damage. Thermal conductivity and electrical resistivity are obviously different in reinforced and non-reinforced mortars due to the inclusions of the metallic fibres. However, after undergoing microwave heating those properties were not noticeably altered nor follow a trend linked to the heating time. It is assumed that the water migration and evaporation processes are the main cause. Although the flexural strength reduction was gradual for non-reinforced mortars until total failure, the reinforced specimens only showed a 13% of reduction for the first 120 s, remaining almost constant afterwards. Although it was proved that the fibres increase the temperature on the specimen surface and its adhesion to the matrix is altered, their crack bridging effect overcomes further damage.